2019
DOI: 10.1002/pssb.201900419
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Stokes Photoluminescence of Monolayer WS2

Abstract: Anti‐Stokes photoluminescence excitation of a WS2 monolayer flake between 10 and 300 K is reported herein. Even with continuous‐wave lasers at low power, the emission of the exciton at excitation 100 meV below its emission energy at room temperature is observed. A mechanism which involves the trions as the intermediate state is proposed, leading to an efficient up‐conversion process. In addition, it is demonstrated that phonons are the source of the additional energy needed by the system. Overall, the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…At room temperature, Jadczak et al found that the power dependence slope of the UPL intensity is close to 1 as well, when the excitation is at A1s energy of WS2. These measurements provide strong evidence that the UPL process in our work is the phononassisted linear up-conversion process [13,14,15,17,23].…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…At room temperature, Jadczak et al found that the power dependence slope of the UPL intensity is close to 1 as well, when the excitation is at A1s energy of WS2. These measurements provide strong evidence that the UPL process in our work is the phononassisted linear up-conversion process [13,14,15,17,23].…”
Section: Resultssupporting
confidence: 59%
“…There have been many studies on UPL of TMDCs, which has been realized by resonant excitation of the ground exciton states [10,11,12] at the cryogenic temperature. Alternatively, by an off-resonance excitation at the lower energy than the exciton states, the phononassisted up-conversion process could be achieved [13][14][15][16][17], which is promising to realize the application of photodetector [17,18,19]. The detailed physical mechanisms of UPL under various extreme conditions are required for multi-environment optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of real intermediate states can be revealed by PLE spectroscopy, which has been discussed in section 2.1 (phonon absorption). When the excitation energy is below the energy of the real intermediate states, the upconversion intensity declines abruptly [75,92].…”
Section: Multiple-photon Absorptionmentioning
confidence: 99%
“…At low laser power before saturation, the PL intensity of two-photon upconversion involving real intermediate states usually shows a quadratic dependence on the excitation power (α ≈ 2) [68,71,73,74,92,105,108]. Further increasing the excitation power results in the full occupation of the intermediate states.…”
Section: Multiple-photon Absorptionmentioning
confidence: 99%
See 1 more Smart Citation